The Virtuous Servant Owner—A Paradigm Whose Time has Come (Again) - Navon, Mois (Frontiers in Robotics and AI, 2021)
Social Robots are coming. They are being designed to enter our lives and help in everything from childrearing to elderly care, from household chores to personal therapy, and the list goes on. There is great promise that these machines will further the progress that their predecessors achieved, enhancing our lives and alleviating us of the many tasks with which we would rather not be occupied. But there is a dilemma. On the one hand, these machines are just that, machines. Accordingly, some thinkers propose that we maintain this perspective and relate to Social Robots as “tools”. Yet, in treating them as such, it is argued, we deny our own natural empathy, ultimately inculcating vicious as opposed to virtuous dispositions. Many thinkers thus apply Kant’s approach to animals—“he who is cruel to animals becomes hard also in his dealings with men”—contending that we must not maltreat robots lest we maltreat humans. On the other hand, because we innately anthropomorphize entities that behave with autonomy and mobility (let alone entities that exhibit beliefs, desires and intentions), we become emotionally entangled with them. Some thinkers actually encourage such relationships. But there are problems here also. For starters, many maintain that it is imprudent to have “empty,” unidirectional relationships for we will then fail to appreciate authentic reciprocal relationships. Furthermore, such relationships can lead to our being manipulated, to our shunning of real human interactions as “messy,” to our incorrectly allocating resources away from humans, and more. In this article, I review the various positions on this issue and propose an approach that I believe sits in the middle ground between the one extreme of treating Social Robots as mere machines versus the other extreme of accepting Social Robots as having human-like status. I call the approach “The Virtuous Servant Owner” and base it on the virtue ethics of the medieval Jewish philosopher Maimonides.